A response of the imbibed dormant red rice caryopsis to biotic challenges involves extracellular pH increase to elicit superoxide production. Issue 4 (24th July 2018) - Ghotbzadeh, Sepideh; Gianinetti, Alberto
Abstract: Seeds often survive in the soil in a dormant state, but their persistence is endangered by micro-organisms that could feed on them. Seed–microbe interactions in the soil are, however, poorly understood. We used dormant caryopses of red rice to study the defence response induced by pronase, a mixture of proteases secreted by Streptomyces griseus, a non-pathogenic bacterium. Pronase was shown to activate the plant immune reaction, indicating that its activity was recognized as a potential microbial attack. The defence reaction included extracellular alkalinization and superoxide production, and the former was necessary to activate the latter, since buffering at pH 6 inhibited the oxidative burst. Alkalinization was sufficient to trigger the oxidative burst, as superoxide production increased when caryopses were incubated in buffered solutions of increasing pH without pronase. Release of proanthocyanidins was observed, with or without pronase. These diverse mechanisms are hypothesized to cooperate in reinforcing seed protection. Finally, time profiles of superoxide production by dormant and non-dormant red rice caryopses during imbibition did not support a relationship between extracellular superoxide and dormancy breaking or germination. Thus, the role of this reactive oxygen species in red rice imbibed caryopses appears to be essentially aimed at defence against attacks by challenging micro-organisms.